Adaptasi Model Latihan Permainan Beladiri Pada Anak-Anak Di Masa Pandemi Covid-19 - Komang Surya Adnyana; Gede Hendri Ari Susila (Purwadita : Jurnal Agama dan Budaya, 2020)
During this pandemic, children are needed as educators to adapt training models to improve their fitness and one of them is a martial arts game training model. Kumite training (fighting) is one of the techniques in the martial arts sport of karate. In the kumite training process, children will be motivated to play attacking techniques such as hitting (zuki) and kicking (geri), parrying techniques (uke), and techniques to avoid opponent attacks. In improving fitness, children can adapt two game training models, such as (1) the zuki hanging ball, this game practice is carried out with the concept of playing with a hanging ball, and (2) hanging ball geri, is an exercise with the concept of playing and using a hanging rubber ball. This activity will at least provide new experiences for children in filling the time in an effort to improve body fitness. Keywords: adaptation; training; games; self-defense; Covid-19